A study to enhance risk management practice in Jabatan Kerja Raya projects - Govindasamy, Yuvabalan (2015)
Jabatan Kerja Raya (JKR) Malaysia has recognized the need to effectively manage risks in order to achieve project objectives in the context of time, cost and quality. Despite practicing risk management based on established policies and guidelines, cost overrun and project delay due to risks still remain a major concern for JKR. Therefore, the aim of this study is to investigate weakness in current risk management practice for JKR projects and establish improvement methods to enhance the practice. Objectives identified to achieve the aim of this study are identify perception and awareness on risk management practice by JKR project team, evaluate weakness in current practice and propose improvement methods to enhance practice. This study was conducted using research methodologies such as literature review, interview with experts and questionnaire survey in order to achieve the objectives identified. A total of 97 questionnaires were collected and analysed using SPSS software to obtain the reliability, average index and relative importance index of the factors established. Findings revealed majority project team have positive perception but low awareness on risk management practice. Among the weakness in > current risk .management practice are JKR project team lacking in understanding and knowledge, risk management not implemented in the planning phase of project, absence of proper risk monitoring and reporting and sufficient resources and budget not provided to JKR project team. Several improvement methods established including giving emphasis on continuous training program, risk management must be applied in the planning phase of project life cycle, JKR top management to provide more support for risk management and developing an automated systematic risk management tool to improve existing practice. Outcome of this study can be used to help JKR project teams to effectively manage risks in their projects thus being able to reduce delays and cost overrun in projects due to risks.